Animal models of intestinal inflammation: clues to the pathogenesis of inflammatory bowel disease. - Powrie, F; Uhlig, H (2004)
In the last decade a number of models of chronic intestinal inflammation have been described that resemble aspects of the pathology found in patients with inflammatory bowel disease. Several themes have emerged from these studies that are of relevance to the pathogenesis of inflammatory bowel disease. Firstly, intestinal inflammation is a consequence of an aberrant chronic immune response triggered by enteric bacteria. Both innate and adaptive immune mechanisms can cause colitis and in many models there is evidence of differential activation of T helper 1 (Th1)-type cells. Targeting the Th1 pathway prevents experimental colitis and there is also evidence that this may be useful in Crohn's disease. Secondly, specialized populations of regulatory T cells have been shown to prevent colitis and in some systems cure it, suggesting immune responses in the intestine are subject to dominant T cell-mediated control. Here we focus on new insights into the pathogenesis and regulation of intestinal inflammation as revealed by model systems and how these may be harnessed for the treatment of IBD.